Transcranial Infrared Laser Stimulation for the Treatment of Traumatic Brain Injury: A Case Series: Transcranial Infrared Laser Stimulation for TBI - Rindner, Elisabeth; Haroon, Jonathan; Jordan, Kaya; Mahdavi, Kennedy; Surya, Jean Rama; Zielinski, Margaret; Habelhah, Barshen; Venkatraman, Victoria; Becerra, Sergio; Chan, Lider; Kuhn, Taylor; Jordan, Sheldon (Journal of Lasers in Medical Sciences, 2022)
Introduction: This study intended to evaluate the safety and possible therapeutic effect of transcranial infrared laser stimulation (TILS) based on photobiomodulation (PBM) among patients with traumatic brain injury (TBI). Methods: Eleven participants were diagnosed with TBI after a full neurological examination and MRI evaluation by a board-certified neurologist completed five to eight 20-minute TILS sessions using the Cytonsys CytonPro-5000 apparatus (pilot laser control, focused wavelength of 1064 nm, maximum output power of 10W, maximum optical power density of 500 mW/cm2, effective area 4.5 cm2 in diameter). Per TILS session, participants underwent a laser dose of 250 mW/cm2 continuous laser wave to each hemisphere using predetermined patient-specific coordinates. Structural imaging was used to neuronavigate individual treatment targets in the frontal cortex (Brodmann area 10). The primary safety measure for this study was the occurrence of adverse events (AEs) or serious adverse events (SAEs). The primary efficacy outcome measure was the participant-rated global rating of change (GRC) post-intervention. Secondary outcome measures included a battery of neuropsychological testing and mood questionnaires done both pre-and post-intervention. Results: All patients enrolled in this study protocol were able to tolerate the study procedures without any AEs or SAEs. Nine out of eleven participants had clinically significant improvements in GRC score (≥ +2). Neuropsychological testing and mood questionnaire outcomes also suggested a positive therapeutic effect. Conclusion: This study provides preliminary evidence supporting the safety and potential efficacy of TILS as a non-invasive clinical intervention for individuals with TBI.